2005
DOI: 10.2208/journalam.8.793
|View full text |Cite
|
Sign up to set email alerts
|

Three dimensional snalysis of flow around a porous spur dike

Abstract: The goal of study described in this paper is to develop the three dimensional analytical model to simulate a flow around a porous structures. The VOF method was used for the free surfacce flow field considering the future applicability to the rapid changes of the flow such as a surge flow. The flow in porous media was modeled by the Brinkman-Forchheimer extended Darcy's equation. As the experimental verification, three dimensional velocities around a spur dike were measured by using Acoustic-Doppler Velocimete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Certain researchers [40] examined permeable spurs as rubble-mound structures using laboratory experiments and a two-dimensional model focusing on the rubble geometry of a group of groins in terms of the flow structure and the flow force. A study [41] examined the three-dimensional flow features around a porous spur dike by developing a three-dimensional analytical model using the k-ε model of turbulence and found some discrepancies downstream of the spur dike. Another study [17] used a laboratory experiment to compare suspended sediment transport in permeable and impermeable spur dike fields and concluded that the suspended sediment concentration decreases in the downstream direction due to sedimentation in the transition zone for permeable spur dikes; they used a staggered group of poles as an individual spur dike.…”
Section: Laboratory Experimentsmentioning
confidence: 99%
“…Certain researchers [40] examined permeable spurs as rubble-mound structures using laboratory experiments and a two-dimensional model focusing on the rubble geometry of a group of groins in terms of the flow structure and the flow force. A study [41] examined the three-dimensional flow features around a porous spur dike by developing a three-dimensional analytical model using the k-ε model of turbulence and found some discrepancies downstream of the spur dike. Another study [17] used a laboratory experiment to compare suspended sediment transport in permeable and impermeable spur dike fields and concluded that the suspended sediment concentration decreases in the downstream direction due to sedimentation in the transition zone for permeable spur dikes; they used a staggered group of poles as an individual spur dike.…”
Section: Laboratory Experimentsmentioning
confidence: 99%